Digital Movement of Opinion #BLACKLIVESMATTER in Creating Public Opinion About Black Lives Matter - Rizky Wulan Ramadhani; Edy Prihantoro (Ikatan Sarjana Komunikasi Indonesia, 2023)
#BlackLivesMatter is still used by netizens to express opinions about the Black Lives Matter movement which is still developing today. In April 2021, the court ruled for Derek Chauvin, the police officer who shot George Floyd. In addition, there are still many shootings of black citizens in the United States and various other countries. This study aims to determine the spread of #BlackLivesMastter and public opinion on Twitter during 20 – 27 April 2021 regarding Black Lives Matter. This research uses a combination of quantitative and qualitative methods. The quantitative method is used to see the distribution of 2,500 sample tweets using Netlytic.org and Gephi. The qualitative method is conducted to analyze public opinion about Black Lives Matter. The theory used is Computer-Mediated Communication, Public Space, and Critical Discourse Analysis. The results showed that opinions were dominated by positive opinions with 71.76%, negative opinions with 13.08% and irrelevant opinions with 15.16%. The positive opinions are dominant because they have succeeded in creating empathy, anger, and criticism, have political interests, and are voiced by political elite accounts, media, NGOs, and celebrities. Negative opinions are voiced by two main political elites and Twitter users who are not well known so they are considered personal opinions. Irrelevant opinions are voiced by Twitter users in more private spaces and are used to attract public attention.